Research on the Influence of Power Grid on the Operation of Voltage Source Inverter - WANG Lucheng; HE Donglin; ZHANG Fengjiang (Kongzhi Yu Xinxi Jishu)
Three-phase input current unbalance is often happened in inverters, which causes devices damaged by overvoltage or over-current. Influences of grid unbalance, line impedance and multi-load on voltage source inverter and their mechanisms were analyzed from the point view of low frequency and power. It presented that three-phase input current unbalance is caused by negative sequence components of grid voltage and makes low frequency harmonic current increased and even devices damaged in inverter. The fact that line impedance affects serial or parallel frequency, input voltage and proportion of input inductive current was pointed out, which is one of the important factors causing the system resonant and devices breakdown by overvoltage. It also proposed that multi-inverter operation would suppress harmonic input currents and the results of theoretical calculation, simulation and practical test showed the correctness of the view point. Moreover, it presented some relative measures, and this can help designers and users to avoid application risks of inverters and improve the stability of the machines.